2021
DOI: 10.1007/s12185-021-03219-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a hospital-at-home (HAH) unit for hematological patients during the COVID-19 pandemic: safety and feasibility

Abstract: Background “Hospital-at-home” (HAH) programs have been shown to optimize resource utilization, shorten hospitalization and prevent nosocomial infection. Methods We retrospectively analysed data regarding implementation of an HAH unit for caring patients with hematological malignancies in our center, during the COVID-19 pandemic. Results Between January and November 2020, 105 patients were treated in the HAH unit for a total of 204 episodes. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In general, and especially since the COVID-19 pandemic, the applications of Hospital at home (i.e., providing acute healthcare in a patient's home as an alternative to traditional inpatient care) have drastically increased [25][26][27]. In patients with heart failure, a metaanalysis indicated that hospital at home significantly increased time to first readmission and improved health-related quality of life compared to routine hospitalization [28].…”
Section: Discussionmentioning
confidence: 99%
“…In general, and especially since the COVID-19 pandemic, the applications of Hospital at home (i.e., providing acute healthcare in a patient's home as an alternative to traditional inpatient care) have drastically increased [25][26][27]. In patients with heart failure, a metaanalysis indicated that hospital at home significantly increased time to first readmission and improved health-related quality of life compared to routine hospitalization [28].…”
Section: Discussionmentioning
confidence: 99%
“…Methods to deliver appropriate medication, infusions, oxygen, DME, physical, and occupational therapy and nutrition can be arranged to support the patient's home hospital stay. [4][5][6][7] In the command center, nurses and others follow the patient's status in real-time. Bi-directional audio/visual connections to the command center make nursing and physician rounds not dissimilar from the brick and mortar model.…”
Section: Acute Hospitalization At Home During the Covid-19 Pandemicmentioning
confidence: 99%
“…3 Covid provided the motivation and urgency for hospitals to rapidly consider implementation of virtual home hospitalization for the care of acutely ill patients.Many hospital systems quickly developed HaH offerings for patients with Covid-19 and other conditions. 2,4,5 For the most part, 2 types of HaH became quickly prominent: Admission Avoidance and Early Supported Discharge. Commercial entities, such as Vilify, Contessa, and Medically Home partnered with health systems to develop remote care command centers and promote rapid implementation of virtual home hospitalization.…”
mentioning
confidence: 99%
“…As the haemato-oncology patient population is especially vulnerable to COVID-19 morbidity and mortality and cancer treatment interruptions, accelerated attempts to employ home care units for anti-neoplastic treatments and supportive care were implemented [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%